Consequence modeling at the Eastman Kingsport site. Issue 4 (24th October 2017) - James, Michael; Skelton, David
Abstract : The intent of this paper will be to review the methods utilized at the Eastman Kingsport site in determining magnitude of consequences of toxic, thermal, and blast overpressure scenarios. This will include discussion on dispersion modeling, dose‐response methods for toxic, and thermal probits as well as assessing occupant vulnerability through the use of BakerRisk's Explosion Risk Cooperative tools. © 2017 American Institute of Chemical Engineers Process Saf Prog 36: 338–352, 2017